Intimate strangers : commercial surrogacy in Russia and Ukraine and the making of truth - Siegl, Veronika, 1985- (Cornell University Press, 2023)
"This book explores the practice of commercial surrogacy in Russia and Ukraine and unpacks the inner workings of this practice that is marked by secrecy, distrust, and (anonymous) business relationships. It illustrates how 'truths' accelerate market expansion into the intimate spheres of life that play out on women's bodies as mothers and workers"--